Displacement and Belonging Come Together in Seamus Heaney’s Poetry, Where he Reflects on Cultural Memory and Personal Identity - Rehan Aslam Sahi; Mudassar Ali; Imran Aslam (`, 2025)
This research article explores the intertwined themes of displacement and belonging in the later poetry of Seamus Heaney, focusing primarily on his collections Station Island (1984), The Haw Lantern (1987), The Spirit Level (1996), and District and Circle (2006). As a poet rooted in the cultural and political landscape of Northern Ireland, Heaney’s later work reflects a growing tension between personal exile and the longing for connection, geographically, spiritually, and historically. The study examines how Heaney’s poetry evolves from a sense of rootedness in rural identity to more complex meditations on spiritual alienation, cultural dislocation, and transitory belonging in an increasingly fragmented world. Through close textual analysis of selected poems such as “Station Island,” “The Disappearing Island,” “District and Circle,” and “Route 110,” the paper illustrates how Heaney navigates personal memory, national trauma, and global modernity. Ultimately, the research reveals that Heaney redefines belonging not as a fixed state but as a dynamic, often uneasy negotiation between place, memory, and identity. Keywords: Displacement, Belonging, Seamus Heaney’s Poetry, Cultural Memory, Personal Identity